Engaging the d/Deaf Audience in Museums: A Case Study at the Calouste Gulbenkian Museum. (2nd July 2016) - Martins, Patrícia Roque
ABSTRACT: This article addresses ways that museums can strengthen programming for d/Deaf audiences. Through the development and study of a tour for a d/Deaf audience conducted through signing and oral translation at the Calouste Gulbenkian Museum in Lisbon (Portugal), the author examines issues of language, identity and inclusion. She argues that the use of sign language is critical, and that Deaf visitors' engagement is enhanced when tours are given by Deaf tour guides. This article highlights common pathways for museums to better relate to d/Deaf and hard of hearing audiences.